Peningkatan Kualitas Rancangan RPP pada Materi Al-Qur'an Hadis dengan Penerapan Pendekatan Sosiokultural di Sekolah Menengah Atas - Munawar, Fuad (Epistemic: Jurnal Ilmiah Pendidikan, 2022)
This study is based on the urgency of integrating a sociocultural approach in the design of lesson plans (RPP) for Al-Quran Hadith material, considering the socio-cultural diversity and social organization backgrounds of students. The objective of this research is to analyze the extent to which Al-Quran Hadith subject teachers at SMA IT Asy-Syakur implement a sociocultural approach in their lesson plans based on a critical review. This research employs a qualitative method with a case study design. Data collection techniques included documentation studies, observations, and interviews. The findings reveal that the majority of teachers still view the creation of lesson plans as an annual routine for school accreditation purposes. This indicates the need for a firm attitude and strong managerial principles from the school principal as a supervisor. However, in teaching practice, Al-Quran Hadith subject teachers have implemented sociocultural-based learning by using their own personalities as concrete examples. These findings highlight the importance of managerial support and enhancing teachers' competencies to optimize the integration of the sociocultural approach in learning.